Gobierno del encuentro: el mito gubernamental en el régimen de Guillermo Lasso a partir de las denuncias del Portal La Posta, enero 2023. - Carpio Maigua, Jonathan Daniel (2024)
The study examines the construction and transformation of the governmental myth of Guillermo Lasso's “Government of Encounter”, affected by the corruption allegations disseminated by “La Posta” in January 2023. The governmental myth is crucial to legitimize power in the daily life of citizens. Initially, Lasso promoted a discourse of renewal and dialogue; however, corruption allegations eroded this discourse and provoked a crisis that transformed this government myth. Through a qualitative analysis of the discourse, semiotics and interviews, we examine the elements that built the myth before and after the accusations, showing that its effectiveness depends on the ability to adapt to different contexts.